Adsorption characteristics of Pb(II) ions on sulfidized hemimorphite surface under ammonium sulfate system - Zhang, Xi; Deng, Jiushuai; Wang, Yu; Li, Sihao; Zhao, Honghui; Liu, Chang; Ma, Zhitao; Sun, Zhenwu (International journal of mining science and technology, 2023)
In this work, the effect of ammonium sulfate on the adsorption characteristics of low-concentration Pb(II) ions on the sulfidized hemimorphite surface was comprehensively investigated. The results showed that ammonium sulfate could increase the maximum recovery of hemimorphite from 69.42% to 88.24% under a low concentration of Pb(II) ions. On the hemimorphite surface pretreated with ammonium sulfate, the adsorption of Pb(II) ions was enhanced and the main species of Pb adsorbed was changed from Pb―O/OH to PbS. This was due to the larger amount of ZnS providing more effective adsorption sites for Pb components to generate PbS. Meanwhile, the intensity of ZnS decreased with the formation of PbS, demonstrating that ZnS was covered by PbS which formed later on the mineral surface. It was beneficial for the adsorption of butyl xanthate on the hemimorphite surface to form more hydrophobic substances. As a result, ammonium sulfate played a crucial role in realizing the efficient recovery of hemimorphite.